Cell Fate - Chin-Hsing Annie Lin (Frontiers Research Topics, 2016)
The fundamental question of how an undifferentiated progenitor cell adopts a more specialized cell fate that then contributes to the development of specialized tissues, organs, organ systems and ultimately a unique individual of a given species has intrigued cell and developmental biologists for many years. Advances in molecular and cell biology have enabled investigators to identify genetic and epigenetic factors that contribute to these processes with increasing detail and also to define the various molecular characteristics of each cell fate with greater precision. Understanding these processes have also provided greater insights into disorders in which the normal mechanisms of cell fate determination are altered, such as in cancer and inherited malformations. With these advances have come techniques that facilitate the manipulation of cell fate, which have the potential to revolutionize the field of medicine by facilitating the repair and/or regeneration of diseased organs. Given the rapid advances that are occurring in the field, the articles in this eBook are both relevant and timely. These articles originally appeared online as part of the Research Topic "Cell Fate" overseen by my colleagues Dr. Lin, Dr. Buttitta, Dr. Maves, Dr. Dilworth, Dr. Paladini and myself and have been viewed extensively. Because of their popularity, they are now made available as an eBook, in a more easily downloadable form. Michael T. Chin